The Coalminers and Their "Red" Union: The Amalgamated Mine Workers of Nova Scotia, 1932-1936 - Earle, Michael (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1988)
Abstract The amalgamated mine workers of Nova Scotia (AMW) was a communist led union of coal miners that broke away from the established United Mine Workers of America (UMW) in the early depression years, at a time when only communists called for trade union militance. The new union adopted principles of extreme rank-and-file democracy and radical resistance to company demands for wage cuts. It held the allegiance of the majority of miners in the province for several years, but its rival, the UMW, was supported by the coal company and the government. Moreover, the AMW never carried out its threats of a district strike to win recognition. After several years of the dual union situation, the miners saw the necessity of unity in confrontations with the company. In addition, the UMW was resurgent in the United States and had begun to take a more militant stance. Finally, changes in the policy of the Communist Party caused it to press for reunification. In rejoining the UMW, however, the miners were obliged to surrender many of their aspirations for district autonomy and inner-union democracy.